Suicide by gunshot in the United Kingdom: a review of the literature. - Haw, C; Sutton, L; Simkin, S; Gunnell, D; Kapur, N; Nowers, M; Hawton, K (2004)
This paper reviews the research literature on gunshot suicide in the United Kingdom and the international literature with reference to strategies aimed at preventing gunshot suicides. Trends in gun ownership and changes in firearm legislation in the UK over the past 20 years are described. Most UK gunshot suicides are male, middle-aged and living with a partner and involve the use of shotguns. They are less likely to have current or past mental health problems, or a previous act of self-harm, than people who commit suicide by other methods, and their suicide is more likely to have been precipitated by a relationship dispute. Where alcohol is consumed the amount tends to be large. The international literature provides evidence of a strong association between rates of gun ownership and gunshot suicide, and some evidence of a reduction in firearm suicide rates following the introduction of restrictive firearm legislation. Over the past 20 years the number of gunshot suicides in the UK has declined by over 50% to a little over a hundred deaths per annum. At the same time, firearm legislation has become progressively more restrictive and rates of gun ownership have declined. Measures, which might further reduce the prevalence of gunshot suicides in the UK, are discussed.